Progress in sustainable energy technologies Vol II : creating sustainable development - Midilli, Adnan; Kucuk, Haydar; Dincer, Ibrahim (Springer International Publishing, 2014)
This multi-disciplinary volume presents information on the state-of-the-art in the sustainable development technologies and tactics. Its unique amalgamation of the latest technical information, research findings, and examples of successfully applied new developments in the area of sustainable development will be of keen interest to engineers, students, practitioners, scientists, and researchers concerned with sustainability.  Problem statements, projections, new concepts, models, experiments, measurements, and simulations from not only engineering and science, but disciplines as diverse as ecology, education, economics, and information technology are included, in order to create a truly holistic vision of the sustainable development field. The contributions feature coverage of topics including green buildings, exergy analysis, clean carbon technologies, waste management, energy conservation, environmental remediation, energy security, and sustainable development policy.